Benefit of routine preprocedural radial artery angiography in STEMI patients. Issue 1 (5th August 2018) - Zafirovska, Biljana; Antov, Slobodan; Kostov, Jorgo; Spiroski, Igor; Vasilev, Ivan; Jovkovski, Aleksandar; Kitanoski, Darko; Petkoska, Danica; Bertrand, Olivier F.; Kedev, Sasko
Abstract: Aims: To assess the benefit of routine preprocedural radial artery (RA) angiography in patients with ST segment elevation myocardial infarction (STEMI). Methods and Results: All consecutive STEMI patients, in the period from January 2010 until December 2016 were included in the study. Preprocedural radial artery angiography was performed in all patients since March 2011. We compared clinical and procedure characteristics, access site bleeding complications and failure of primary chosen TRA between two groups of STEMI patients before and after we started performing routine RA angiography. We compared 762 STEMI patients from 2010 until March 2011 and 4306 STEMI patients after March 2011 until December 2016. Mean age of patients was 60 ± 11 years with 73% males. The latter group had more elderly and obese patients ( P < .0001 both). Prior percutaneous coronary interventions was present in 7% of patients and 0, 1% had prior coronary bypass surgery. Procedure duration (38 ± 16 vs. 32 ± 20 min) was significantly longer in the first group ( P value < .0001), but contrast volume (120 ± 33 vs. 110 ± 35 ml), and fluoroscopy time (8.6 ± 6 vs. 8.7 ± 8 min) were similar in both groups. Access crossover from primary TRA was 4, 6% in the first group, with a significant decrease to 3, 1% in the second ( P < .0001), after introducing preprocedural RA angiography. Access site bleeding complications were significantly higher in the first group 6.8% vs. 4.3% in the second (p < .0001). Conclusion: Routine preprocedural radial artery angiography in STEMI patients is associated with lower rate of access site bleeding complications and reduced overall procedural time and TRA crossover rate.